Qur’anic Concept of Mawaddah: Theological Foundations and Its Implications in Muslim Societies - Dr Hafiz Saeed Ahmad; Dr. Atiq-Ur-Rehman (Al Manhal Research Journal, 2025)
This paper examines the Quranic concept of Mawaddah (love and affection) and its implications for the spiritual, social, and ethical aspects of Muslim life. As a foundational principle embedded in the Quran, Mawaddah serves not only as a theological value but also as a practical framework for interpersonal and communal conduct within the Muslim Ummah. The study addresses the pressing need to revisit this concept in light of contemporary global challenges, aiming to underscore its enduring relevance in fostering compassion, unity, and justice. Employing a multidisciplinary methodology, the research integrates Quranic exegesis, linguistic analysis, and historical-contextual interpretation with contemporary sociological insights. It begins with a close reading of key Quranic verses, exploring their linguistic features and exegetical interpretations. The study then traces the application and evolution of Mawaddah across classical and modern Islamic thought, highlighting its universal scope across various traditions and schools. Drawing on variety of interpretations, the paper examines how Mawaddah influences contemporary Muslim social life, from family relations to global solidarity. It also evaluates the concept’s potential as a guiding ethical principle in addressing modern issues such as religious pluralism, social justice, and governance. The study concludes that Mawaddah is a dynamic and transformative element of Islamic spirituality, offering critical insights for scholars, religious leaders, and policymakers seeking to promote a holistic and humane understanding of Islam in today’s interconnected world.